Phylogeny, evolution and ecological speciation analyses of Imperata (Poaceae: Andropogoneae) in the Neotropics. Issue 6 (18th August 2021) - Cordobés, Fernando Moro; Robbiati, Federico Omar; Anton, Ana María; Scrivanti, Lidia Raquel
Abstract : Imperata is a ubiquitous grass genus of the tribe Andropogoneae (Poaceae), distributed throughout the world. Previous systematic studies had established that the genus encompasses nine species although no phylogenetic molecular studies are available in which all the taxa have been included. The American continent has the largest number of species, encouraging research into how these taxa have evolved. Here we present a phylogenetic analysis based on three plastids ( ndhF, trnL-F, and atpB-rbcL ) and one nuclear (ITS) marker that cover the most extensive geographic distribution of the genus. We use this phylogeny to test the monophyly of Imperata within tribe Andropogoneae, analyze the infrageneric relationships of the genus, and estimate lineage divergence time. Additionally, ecological niche models (ENM) of the American lineages are presented to recognize the abiotic factors that constraint their potential geographic distribution and allow an understanding of the ecological drivers for species diversification. Our results yield a fully supported tree where monophyly is confirmed for the genus and exposes the existence of two clades, one encompassing five American lineages and the other encompassing those of the rest of the world. In parallel, molecular dating, ENM, and ecological speciation tests suggest that American lineages underwent speciation during the Quaternary associated with conservatism and niche divergence. Our results contribute to both the taxonomic and to the evolutionary knowledge of grasses, and also to the understanding of the biological diversity in the Neotropics.